Status asthmaticus in the past and nowadays - Droszcz, Wacław (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
The problem of status asthmaticus in the past and nowadays is discussed. This phenomenon in the recent period has diminished markedly.